The prevalence of restless leg syndrome among pregnant Saudi women - Khan, Mohmd; Mobeireek, Noha; Al-Jahdali, Yassar; Al-Dubyan, Nujood; Ahmed, Anwar; Al-Gamedi, Majed; Al-Harbi, Abdullah; Al-Jahdali, Hamdan (Avicenna Journal of Medicine, 2018)
Objectives: Restless legs syndrome (RLS) is common among pregnant women, but it has not been documented in pregnant Saudi Arabian women. The main purpose of this study was to estimate the extent of the prevalence of RLS and identify both the associated factors and the associated risk factors among pregnant Saudi women. Methods: A cross-sectional study was conducted among pregnant women visiting obstetric clinics at King Abdulaziz Medical City in Riyadh (KAMC-Riyadh) over the period from June 1 to November 1, 2014. We interviewed the participants and collected demographic data, number of pregnancies, duration of pregnancy, comorbidities, and symptoms of RLS. The diagnosis of RLS is based on the four criteria designated by the International RLS Study Group. Results: The total number of participants enrolled was 517, and the mean age was 30.11 ± 5.42 years. The prevalence of RLS was 21.3% (110/517) (95% confidence interval [CI]: 17.83%-25.06%). RLS symptoms were more common among women in the third trimester (24.1%) compared to the second trimester (14.3%) and first trimester (13.6%), P = 0.043. The stepwise multivariate logistic model identified insomnia (odds ratio [OR]: 3.6, 95% CI: 2.167–6.017, P = 0.001), and poor sleep quality (OR: 4.9, 95% CI: 1.473-16.454, P = 0.010) were associated with RLS. Conclusion: RLS occurs in two of ten pregnant women visiting obstetric clinics at KAMC-Riyadh and is strongly associated with insomnia and poor sleep quality. Studies are needed to explore the causality of these associations.
Keywords: Body mass index; Epworth Sleepiness Scale; excessive daytime sleepiness; Pitts; restless legs syndrome; the International Restless Legs Syndrome Study Group